Experimental methodology for quantitative assessment of heat-wrap thermal transient behavior. (July 2019) - Santangelo, Paolo E.; Santunione, Giulia; Muscio, Alberto
Highlights: Test setup and procedure developed for quantitative comparison of heat wraps. Focus on evaluating the thermal transient trend. Testing of commercial heat wraps for low back and neck pain treatment. Statistical analysis supported repeatability and robustness of this approach. Four phases highlighted throughout heat-wrap lifetime. Abstract: Among the numerous thermotherapy methods, heat wraps have been largely used over the last 2 decades as a self-administered practice for pain relief. Therefore, understanding their performance has become instrumental within the healthcare industry. However, the majority of the available studies have been focused on in vivo clinical performance, whereas a standardized, quantitative approach to evaluate and compare the various heat-wrap types against each other is lacking. An experimental methodology is proposed to carry out a comparative assessment between heat wraps in terms of their transient thermal behavior. A simple setup was developed to measure wrap/substrate interface temperature trend. The approach was validated by a preliminary infrared-thermography assessment and statistical analysis on the extensive dataset acquired on commercial heat-wrap types for low-back and neck pain relief. The heat-release trend was found to be qualitatively similar over all the investigated types, consisting of rapid growth, stationary phase, decay and end of the reactions. A set of parameters is also proposed to summarize heat-wrap thermal performance.